Seismic Hydrodynamic Pressure on Concrete Bridge Pier with Submerged Depth from a Set of Shaking Table Model Tests. Issue 2 (October 2020) - Liu, Haiming; Tao, Xiaxin; Tao, Zhengru; Qin, Yifang
Abstract: To study the variation of hydrodynamic pressure on concrete bridge pier with submerged depth in water, a series of shaking table model tests are completed recently. The result shows that the pressures increase with submerged depth obviously with a similar rate for all pier models, input direction combinations and total water depths. The hydrodynamic pressures and the rates increase with the total water depth and input intensity. The pressures on the three models with cross section, rectangular, elliptic and variable rectangular, are varied and different from the provision on the shape coefficient of pier in seismic design codes of highway bridges. The effect of the absorbing stuff adopted in the tests to reduce the potential reflection wave is not obvious. The result suggests to fix more sensors not only at central and but also along the edge lines, to examine the potential horizontal variation of pressures on upstream faces of the piers with different section shapes and the reflected wave must be eliminated with some new way in future test to close to the reality.